MODEL POLA KEANGGOTAAN PADA KOPERASI SIMPAN PINJAM DI KECAMATAN AMBULU KABUPATEN JEMBER - Koko Denik Wahyudi (Majalah Ilmiah DIAN ILMU, 2014)
This study aims to determine how the pattern of membership in the credit union. The research was conducted on credit unions in the District Ambulu Jember which had stood for over 4 years and have done RAT in March 2012. Then taken 2 cooperatives as the research object, namely a cooperative which has the greatest capital and the capital among small cooperatives that meet these criterias. The informant who was the source of the data in this study consisted of (a) Key informant, namely cooperative management in the capture 1 person who has the most dominant role in the management of the cooperative. (b) Other informants, namely (1) the regulatory body, in this case will be taken coordinator supervisor, (2) members of the cooperative, in this case had been selected as 3 members of the group member with the greatest savings, and most had small. Data collection was performed by several techniques, namely (1) in-depth interviews, (2) observation, (3) documentation. The data that had been collected was analyzed using analysis interpretative, the existing qualitative data using an interactive model which consists of 3 main steps: (1) data reduction; (2) the presentation of data, (3) drawing conclusions or verification. The results of this study indicate (1) pattern cooperative membership is not only related to the entry and exit of members but it is also associated with the level of participation of members, (2) Participation of members in capital accumulation and utilization of loan services on the pattern membership open higher as compared with the pattern enclosed membership, (3) Prospective members only used as a condition for the loan application, not as a requirement for acceptance into the member.